Effects of a Forgiveness Intervention on Lesbian and Gay Adolescents Hurt by Homophobia - (:unkn) unknown (My University, 2013)
The purpose of this study was to explore the impact a group level intervention based on Robert Enright's (2001) forgiveness model would have on LGBT adolescents hurt by homophobic offenses. The purposive sample consisted of 26 LGBT- identified adolescents recruited from community-based organizations located in the Midwest and randomly placed in either an experimental group or a wait-list control group. The group intervention consisted of six weekly sessions, each lasting 90 minutes. Participants completed an assessment battery that measured levels of forgiveness and mental health symptomology at three time points: pre-intervention, post-intervention, and approximately one month after completion of the intervention. The researcher ran two separate analyses: (1) a comparison of mean differences between the experimental and wait-list turned experimental group, and (2) a pre-test/post-test comparison of a sample created by combining the experimental and wait-list groups. Similar analyses were completed to compare racial/ethnic differences among the sample. Results from the first data analysis indicated that the experimental group improved significantly on levels of anxiety and on the Enright Forgiveness Inventory One Item Scale Score, but no statistically significant differences were found on the other measures. The waitlist turned experimental group experienced a significant improvement on Enright Forgiveness measures only. The second analysis produced data that found significant improvements on all forgiveness and mental health measures. Implications of this study and recommendations for future researchers wanting to implement a similar program are discussed.
Keywords: Forgiveness; Homophobia; LGBT